1907 S.D. Sess. Laws 113-14, ch. 86, § 54, pt. 53. - (:unkn) unknown (General Publisher, 1907)
To regulate and prevent the storage of gunpowder, tar, pitch, resin, coal oil, benzine [sic], turpentine, hemp, cotton, nitro-glycerine, petroleum, or any of the products thereof, and other combustible or explosive material, and the use of lights in stables, shops and other places, and the building of bonfires, also to regulate and restrain the use of fireworks, fire crackers, torpedoes, roman candles, skyrockets, and other pyrotechnic displays.
--
Keywords: GUN POWDER STORAGE